Development of a Water-Dispersible Phytosterol Nanodispersion System and its Application in Soy Milk Storage - Leong, Wai Fun (2010)
This work was aimed to develop a stable water-dispersible phytosterol nanodispersion system. In the first part of this work, the formation and characterization of phytosterol nanodispersions prepared using Tween 20 was investigated. The experiment demonstrated the feasibility of phytosterol nanodispersion production using hexane as organic phase through an emulsification-evaporation technique. The mean particle diameter of phytosterol nanoparticles produced was 50 nm in diameter and had a spherical shape. The dispersed phase ratio, conventional homogenization parameters and the homogenization pressure showed significant (p < 0.05) effects on the final phytosterol particles size and their distribution profiles. High-pressure homogenization caused significant phytosterol loss (p < 0.05). Two response surface methodology (RSM) processes were applied to optimize the processing and formulation parameters for preparing phytosterol nanodispersions. The optimized processing parameters were 15.25 min of mixing time, 7000 rpm of mixing speed and a homogenization pressure of 42.4 MPa. The corresponding responses for the optimized preparation conditions were a mean particle size (PS) of 52 nm and a phytosterol concentration (Phyto) of 336 mg/l. The optimized formulation parameters determined were a phase ratio (PR) of 3.54 and a mixture ratio (MR) of 0.19, and the corresponding optimized responses were a PS of 55.4 nm and 87.6% phytosterol concentration. The PS showed no significant (p > 0.05) change over a period of 8 weeks of storage at 4 ºC. The Tween 20 was replaced by four different types of sucrose fatty acid esters (SEs), namely sucrose palmitate (P-1570), sucrose laureate (L-1695), sucrose steareate (S-1570) and sucrose oleate (OWA-1570). The physicochemical properties of SE-stabilized water-dispersible phytosterol nanodispersions were examined. The PS and the %Phyto of the prepared phytosterol nanodispersions ranged from 2.8 to 259.9 nm And from 230.4 to 504.6 mg/l. All of the prepared phytosterol nanodispersions exhibited pseudoplastic flow behavior, with a low yield stress ranging from 0.630 to 9.183 mPas and a low consistency coefficient of 0.608 to 88.710 mPas. Less than 1.5 ppm of hexane residues in the prepared nanodispersions was detected. Sucrose esters P-1570, L-1695 and S-1570 were found to be appropriate for use in preparing phytosterol nanoparticles with small PS at a monomodal distribution, with high clarity. The high phytosterol-loaded nanodispersions prepared with co-solvents ethanol and L-1695 had small spherical PS of approximately 5 nm, with low viscosity and high clarity. The solvent residue levels in the final prepared nanodispersions were acceptable. L-1695 was selected for further optimization of the production of L-1695-stabilized water-dispersible phytosterol nanodispersions through RSM. The optimized parameters were 5.5% of Ph (phytosterol concentration), 1.0% of L (L-1695 concentration), 3 C (homogenization cycle), and P(homogenization pressure) of 37 MPa. The corresponding responses for the optimized condition were a PS of 3 nm and a %Ph of 90.4%. The optimized phytosterol nanodispersions had a polydispersity index of 0.550 at a monomodal distribution. The pH value and hexane and ethanol residues concentration were 6.45, 48.2 μl/l and 930.3 μl/l, respectively. The optimized nanodispersions were stable to heat treatment up to 121 °C, chilling at 4 and 10 °C and freezing with a cryoprotectant at – 4 and – 20 °C. The stability of the optimized phytosterol nanodispersions and phytosterol-fortified soy milk (SMP) over a 12-week period was investigated. The storage resulted in increases in PS and reduced the total phytosterol concentration of the autoclaved phytosterol nanodispersions. Adding phytosterol nanodispersions increased the mean particle size of the soy milk. The fortified phytosterol nanoparticles became entrapped in the fat droplets of the soy milk. The stability of the SMP depended on the stability of the soy milk. The fortification of phytosterol nanodispersions in soy milk was feasible.